The Sydney AFF Score: A Simple Tool to Distinguish Females Presenting With Atypical Femur Fractures Versus Typical Femur Fractures. (16th February 2021) - Crouch, Gareth; Dhanekula, Nitesh D; Byth, Karen; Burn, Emma; Lau, Sue Lynn; Nairn, Lillias; Nery, Liza; Doyle, Jean; Graham, Edward; Ellis, Andrew; Clifton‐Bligh, Roderick J; Girgis, Christian M
ABSTRACT: Atypical femur fractures (AFF) are a rare but serious complication of long‐term bisphosphonate use. Although clearly defined by ASBMR criteria, a proportion of patients with AFFs may go unrecognized and the use of qualitative fracture criteria may lead to uncertainty in AFF diagnosis, with significant therapeutic implications. A score that rapidly and accurately identifies AFFs among subtrochanteric femur fractures using quantitative, measurable parameters is needed. In a retrospective cohort of 110 female patients presenting with AFFs or typical femur fractures (TFFs), multiple logistic regression and decision tree analysis were used to develop the Sydney AFF score. This score, based on demographic and femoral geometry variables, uses three dichotomized independent predictors and adds one point for each: (age ≤80 years) + (femoral neck width <37 mm) + (lateral cortical width at lesser trochanter ≥5 mm), (score, 0 to 3). In an independent validation set of 53 female patients at a different centre in Sydney, a score ≥2 demonstrated 73.3% sensitivity and 69.6% specificity for AFF (area under the receiver‐operating characteristic curve [AUC] 0.775, SE 0.063) and remained independently associated with AFF after adjustment for bisphosphonate use. The Sydney AFF score provides a quantitative means of flagging female patients with atraumatic femur fractures who have sustained an AFF as opposed to a TFF. This distinction has clear management implications and may augment current ASBMR diagnostic criteria. © 2021 American Society for Bone and Mineral Research (ASBMR).